Iatrogenic Iliofemoral Vein Dissection: A Rare Complication of Femoral Artery Puncture. (August 2018) - Le, Trong Binh; Kim, Jun Ho; Park, Keun-Myoung; Jeon, Yong Sun; Hong, Kee Chun; Cho, Soon Gu
Iatrogenic iliac vein dissection secondary to femoral artery puncture is a rare complication that has not yet been documented. A 55-year-old woman presented to our institution with acute right iliofemoral thrombosis 2 weeks after transfemoral cerebral angiography. She was previously healthy and was not taking any medication. Right iliofemoral vein dissection was diagnosed by computed tomography angiography and confirmed by conventional venography. The patient was treated endovascularly with stent insertion, and the venous outflow was patent on the 6-month follow-up computed tomography angiogram.